2018
DOI: 10.1088/1748-9326/aa9c6d
|View full text |Cite
|
Sign up to set email alerts
|

The neglected social dimensions to a vehicle-to-grid (V2G) transition: a critical and systematic review

Abstract: Vehicle-to-grid (V2G) refers to efforts to bi-directionally link the electric power system and the transportation system in ways that can improve the sustainability and security of both. A transition to V2G could enable vehicles to simultaneously improve the efficiency (and profitability) of electricity grids, reduce greenhouse gas emissions for transport, accommodate low-carbon sources of energy, and reap cost savings for owners, drivers, and other users. To understand the recent state of this field of resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
0
7

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(106 citation statements)
references
References 111 publications
(114 reference statements)
2
72
0
7
Order By: Relevance
“…This process is intended to identify and explore studies that may exist across different bodies of evidence and contain heterogeneous methodologies (Greenhalgh et al 2005). As Sovacool et al explain, 'a review becomes 'systematic' when it is based on a clearly formulated question or topic, identifies relevant studies, appraises their quality or relevance and then summarizes their evidence' (Sovacool et al 2018). For this reason, qualitative systematic reviews such as this one have been indicated for exploring issues in which multiple and/or competing factors may interact in complex causal relationships (Tranfield et al 2003).…”
Section: Systematic Approachmentioning
confidence: 99%
“…This process is intended to identify and explore studies that may exist across different bodies of evidence and contain heterogeneous methodologies (Greenhalgh et al 2005). As Sovacool et al explain, 'a review becomes 'systematic' when it is based on a clearly formulated question or topic, identifies relevant studies, appraises their quality or relevance and then summarizes their evidence' (Sovacool et al 2018). For this reason, qualitative systematic reviews such as this one have been indicated for exploring issues in which multiple and/or competing factors may interact in complex causal relationships (Tranfield et al 2003).…”
Section: Systematic Approachmentioning
confidence: 99%
“…These observations are also summarised in a review by Sovacool et al [6]. However, the authors point out that the social dimension of V2G is greatly overlooked in scientific studies.…”
Section: Discussionmentioning
confidence: 93%
“…Over the past two decades, there has been considerable research interest in the idea that electrified vehicles could offer benefits to both the transport and power sectors when a sector coupling is achieved [5,6]. In essence, the concept of vehicle-to-grid (V2G) involves the bidirectional flow of electricity between power grids and various forms of transport in a manner that is mutually beneficial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…demand response services in the forms of strategic charging and possibly also discharging the EV batteries back to the grid (i.e. vehicle-togrid; V2G) [12].…”
Section: Introductionmentioning
confidence: 99%